Efeitos do treinamento intervalado de alta intensidade (HIIT) na variabilidade da frequência cardíaca de corredores - Lima, fanny Gonçalves de (2021)
Introduction: Running is among the most popular physical sports activities in the world. For the best performance and recovery of athletes, the training program must be well structured and encourage ideal adaptations to the training load. Evidence supports the positive effect of exercise programs based on High Intensity Interval Training (HIIT) to improve the physical performance of running athletes. Measures of heart rate variability (HRV) have been used to identify changes in autonomic regulation induced by training. Being a useful tool and able to monitor the responses to training loads, physical conditioning or overreaching in athletes during the competitive period or not. Objective: To analysis the HRV and performance of runners submitted to a HIIT protocol. Methods: Eleven runners participated in the study, aged between 31± 5.78 years, well trained with an average experience of 10.23±6.11 years and best time in a running test in a distance of 5 km of 16.94±1.82 minutes. The Maximum Incremental Test was performed on a treadmill, before and after the training program, to calculate the Maximum Aerobic Speed (VAM). After a previous warm-up, the test started at a speed of 10 km/h with an increment of 1 km/h of load every 2 minutes, without pauses between stages. The training lasted four weeks, with two weekly sessions, with the training intensity being readjusted with progressive loads each week. The stimuli were for 1 minute at the speed corresponding to % of VAM, followed by 1 minute of active recovery at 50% of %VAM, until voluntary exhaustion or up to the established ceiling of maximum 90 minutes for training sessions. RR Interval data were recorded at rest by the POLAR® RS800cx heart rate monitor, at 4 different times: before the initial maximum incremental test (PRE HIIT), before the first training session of week 3 (110% of VAM), before the first week 4 training session (Taper) and before the final incremental test (POST HIIT). HRV analyses were performed using Kubios® software in time domains, non-linear parameters and HRV overview parameters. Statistical analysis was performed using the following tests: Student's t (VO2 max and VAM); One Way ANOVA (rest HRV) and Tukey and Dunn post hoc multiple comparisons. Results: We evidenced positive responses to the proposed training protocol, with maintenance of cardiorespiratory fitness (VO2 max., VAM) and HRV at rest. We observed an adaptation of the cardiac autonomic modulation to the training load, with a reduction in the values of the HRV variables at 110% VAM and Taper moments, and an increase in the POST HIIT moment, approaching the values obtained in the PRE HIIT. Statistically significant differences were observed with p<0.05 in the indices: SDNN(ms): reduced in 110% VAM (34.93±15.87) and Taper (34.29±12.83) compared to PRE HIIT (57.34 ±36.72); RMSSD(ms): reduced in Taper (36.04±13.43) compared to POST HIIT (49.67±19.35); SD2(ms): reduced in Taper (40.05±18.15) compared to PRE HIIT (68.11±43.97). Conclusion: The HRV of runners is sensitive to the effects of HIIT, being efficient to monitor cardiac and autonomic regulation adjusts the training load. We also evidence that HIIT is efficient for the maintenance of the athletes' performance.